Does certified organic agriculture increase agroecosystem health? Evidence from four farming systems in Uganda. Issue 2 (4th March 2018) - Templer, N.; Hauser, M.; Owamani, A.; Kamusingize, D.; Ogwali, H.; Mulumba, L.; Onwonga, R.; Adugna, B. T.; Probst, L.
ABSTRACT: Over the past decades, the number of certified organic farms have increased significantly in Uganda. One assumption is that certified organic agriculture contributes to economic, social and ecological health of agroecosystems. In the literature, however, there is thin empirical evidence to support such claims. We therefore developed health indicators and contrasted data from four Ugandan farming systems with principles and objectives of organic agriculture. We identified four health patterns (ecology-driven, economically struggling, socially-driven, and hanging in) demonstrating the impact of farm management on agroecosystem health and trade-offs between health domains. Ecological farm health is strengthened only if the conversion goes beyond 'organic by default'. Market-oriented specialization can create lock-in situations if production strategies cannot be changed easily. Food shortages occur when additional income from certified production does not compensate for the reduced area and effort devoted to food crops. We conclude that the positive effects of organic certification on agroecosystem health cannot be taken for granted. Interventions promoting organic agriculture should acknowledge risks smallholder farmers take by converting to cash crop-oriented certified organic farming. A challenging question will be how aspects of wellbeing and social health can be translated into certification standards and thus product attributes.